Towards an Australian Bioregionalisation Atlas: A provisional area taxonomy of Australia’s biogeographical regions - Ebach, Malte C.; Gill, Anthony C.; Kwan, Alan; Ahyong, Shane T.; Murphy, Daniel J.; Cassis, Gerasimos (Zootaxa, 2013)
The large number, definition, varied application and validity of named Australian biogeographical regions reflect their ad hoc development via disparate methods or case study idiosyncracies. They do not represent a coherent system. In order to resolve these uncertainties an Australian Bioregionalisation Atlas is proposed as a provisional hierarchical classification, accounting for all known named areas. This provisional area taxonomy includes a diagnosis, description, type locality and map for each named area within the Australian continent, as well as a first-ever area synonymy. Akin to biological clas-sifications, this Atlas seeks to provision universality, objectivity and stability, such that biogeographers, macroecologists and geographers, can test existing areas as well as proposing novel areas. With such a formalised and comparative system in place, practitioners can analyse the definition and relationships of biotic areas, and putatively minimise ad hoc expla-nations.